Oral nanoliposome in postoperative home care of patients with myelitis: Treatment and care of acute myelitis - Xie, Lei; Cai, Xiujuan; Yin, Yanhua (Cellular and Molecular Biology, 2023)
Acute myelitis (AM) mainly presents with paralysis, and sensory and autonomic dysfunction, which affects the daily life and quality of life (QoL) of patients. Reasonable selection of treatment and nursing can promote the recovery of patients. It was to explore the effect of oral nanoliposomes combined with home care on the rehabilitation of patients. A total of 100 AM patients who received surgical treatment were enrolled. According to the treatment and nursing methods, they were grouped into a control (oral administration of nanoliposomes plus routine nursing, n=50) and an observation group (oral administration of nanoliposomes plus home care, n=50). Differences between patients’ neurological recovery, lower limb muscle strength, activities of daily living, QoL, and satisfaction with quality of care were assessed. As against control, the time of muscle strength to level 2, urination recovery time, walking time, and sensory recovery time was shorter, and the degree of lower limb muscle strength recovery was higher, the Barthel and Newcastle Satisfaction with Nursing Scale (NSNS) scores of daily living ability increased, and the QoL EuroQol-5 dimensions (EQ-5D) score decreased in the observation group (P<0.05). Oral administration of nanoliposome plus home care can promote the recovery of lower limb muscle strength, improve daily living ability and QoL, and improve nursing satisfaction in patients with AM surgery.